MOTIVASI SISWA DALAM PEMBELAJARAN SENI TARI DI SMP NEGERI 3 KOTO BARU KABUPATEN DHARMASRAYA - Zaidayani Zaidayani; Yuliasma Yuliasma; Idawati Syarif (FBS Universitas Negeri Padang, 2013)
Absract This research aimed at describing students’ motivation in learning dancing at SMP Negeri 3 Koto Baru Kabupaten Dharmasraya. The objects of this research were the students of VIII.1 at SMP Negeri 3 Koto Baru Kabupaten Dharmasraya. Their motivation in learning dancing was related to both intrinsic and extrinsic motivation. The design of this research was qualitative research. The data was done in 2012/2013 at SMP Negeri 3 Koto Baru Kabupaten Dharmasraya. The data were obtained from observation, interview, and literature review. The findings of this research showed that there were some indicators in both intrinsic and extrinsic motivation for students in learning dancing. The indicators of intrinsic motivation were attendance, attention, motion, question, and exercises. The indicators of extrinsic motivation were compliment and punishment. Kata kunci : motivasi, dalam, pembelajaran, seni, tari